Modern Methods of Integrated Teaching in Primary Classes - Bakhtiorovna, Adizova Nodira; Rustamovna, Bakhronova Shakhnoza (International Journal of Formal Education, 2025)
This article discusses the advantages of integration, how it positively affects students, what modern methods are used in integrated lessons in elementary grades, and how to improve the skills of future elementary teachers in integrated education. Information about popularized and modern methods and technologies is given for skillful passing.